Application of Technological Prospection in the Case Study of the Insole With Diabetic Feet Sensors - Cortinhas, Luciana Maria de Oliveira (2018)
The present article carries out a technological prospection of the technology titled "sensorized footbed for diabetic feet", owned by the University of Brasilia Foundation, in order to analyze the viability of maintaining its patent application due to the current scenario of budget crisis. Similar technologies have been mapped, in Brazil and abroad, that use bioelectrical signals, in the body or in its parts, for monitoring. The search for patents was based on Orbit. We also analyzed publications on electronic monitoring systems in the databases of the Scopus and Web of Science platforms. It was identified that the area presented growth in the last years, but that the studies are still incipient. The study also aimed at evaluating the technological maturity of the invention, so it was concluded that the degree of technological readiness of the insole studied is TRL 5.